Photocatalytic degradation of cefazolin over N-doped TiO2 under UV and sunlight irradiation: Prediction of the reaction paths via conceptual DFT - Gurkan, Yelda Yalcin; Turkten, Nazli; Hatipoglu, Arzu; Cinar, Zekiye (ELSEVIER SCIENCE SA, 2012)
Cefazolin is a semi-synthetic antibiotic found in aqueous environments as a pollutant due to its widespread use. The photocatalytic degradation of cefazolin was investigated in aqueous N-doped and undoped-TiO2 suspensions under both UV and sunlight irradiation. N-doped TiO2 photocatalysts with different nitrogen contents were prepared by an incipient wet impregnation method. Characterization of the N-doped samples was performed by SEM-EDX, XRD, UV-DRS, XPS, Raman spectroscopy and surface area (BET) measurements. Degradation of cefazolin was achieved with the use of UV/TiO2. 53% degradation was obtained in 60 min. A higher photocatalytic activity for the degradation of cefazolin was obtained for the N-doped TiO2 compared to Degussa P25. 76% of cefazolin was degraded in 50 min. The N-doped TiO2 also exhibited substantial photocatalytic activity under direct sunlight irradiation, with 80% of cefazolin removed in 30 min. The photocatalytic degradation reaction of cefazolin was monitored by HPLC and FT-IR analyses. The photocatalytic degradation mechanism of cefazolin was determined by the application of the conceptual DFT. The DFT descriptors combined with the experimental results indicate that degradation of cefazolin occurs through intramolecular beta-lactam, thiadiazole, tetrazole and dihydrothiazine ring cleavages followed by subsequent reactions with (OH)-O-center dot radicals transforming the fragments into smaller species such as SO42-, NO3- and NH4+. The predicted mechanism was confirmed by comparison with the experimental results on simple structures reported in the literature. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TiO2; Nitrogen doping; Cefazolin; Heterogeneous photocatalysis; Sunlight; UV-light; ADVANCED OXIDATION PROCESSES; PHOTOELECTROCHEMICAL PROPERTIES; ORAL CEPHALOSPORIN; MATRIX-ISOLATION; PHARMACEUTICALS; WATER; REMOVAL; ISOMERIZATION; DICLOFENAC; MECHANISM; Engineering